Comparative study of on-demand and daily use of sertraline in treatment of premature ejaculation: A randomized clinical trial - Siroosbakht, Soheila (Asian J Urol, 2021)
OBJECTIVE: The intravaginal ejaculatory latency time (IELT) may increase less in on-demand compared to daily intake, but may fulfill a suitable treatment for specific patients. We decided to compare the efficacy and safety of on-demand and daily use of sertraline in order to find the most effective and least complicated method in treatment of premature ejaculation (PE). METHODS: This study was parallel or concurrent control randomized clinical trial. Two hundred and forty patients with PE diagnosed by urologist in the two groups of 120 from July 2017 to February 2019 enrolled in the study. In the first group, it is prescribed 50 mg sertraline each 12 h daily and the second group received 50 mg 4 h before coitus for 4 and 8 weeks. The IELT before treatment and during all coitus after treatment were recorded by the patient's wife with a stopwatch. RESULTS: Mean IELT before, 4 and 8 weeks after treatment in two groups were: On-demand group 101.62±65.44 s, 208.75±128.02 s and 265.87±145.70 s; daily use group 102.50±81.22 s, 276.87±181.08 s and 353.75±176.45 s, respectively. The ejaculation time increased significantly in both groups (p<0.05). However, increase in ejaculation time in daily use group was significantly higher than the on-demand group in 4 weeks (p=0.036), especially in 8 weeks (p=0.009). The percent of side effects in daily use group (26.7%) was higher than on-demand group (20%) (p<0.05). Drowsiness, diarrhea and vertigo were significantly higher in the daily use than on-demand (p<0.05). CONCLUSIONS: On-demand and daily use of sertraline are effective and usually have no serious complications, but the on-demand method is considerably more tolerable. In patients who did not tolerate to daily use of this drug, on-demand could be used as a salvage therapy.